Pelatihan Menjaga Pola Hidup Sehat di Masa Pandemi COVID-19 kepada Inspiring Share Community - Yayuk Yuliarsi; Goalbertus; Astrya Fitryanur; Andrian Nova Fitri; Meini Faudah Amin (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2022)
Inspiring Share Community is a community that was founded in early January 2019 by a group of young people with the same vision of contributing to society. The uncertain condition of the COVID-19 pandemic has made this community commit to be able to do more by educating the public on healthy lifestyles, but the background of most community members who are not from the health sector is an obstacle to realizing this commitment. They do not have sufficient knowledge and skills to be able to take care of their own health so that they feel unable to provide education about healthy lifestyles to the community. Based on this, FKG Usakti provided Training on Maintaining a Healthy Lifestyle during the COVID-19 Pandemic to the Inspiring Share Community. Community members were given education on how to maintain oral health, as well as physical and mental health during the COVID-19 pandemic, besides that, they were also taught how to educate the public about healthy lifestyles using leaflets and how to brush teeth using dental models. The training is carried out online using the Zoom media because the COVID-19 pandemic is still ongoing. Pre and post-test were given to all participants to determine the success of the training. The results of the paired T-test showed a significant increase in the knowledge of community members between before and after the training. Further training with different topics should be carried out offline in order to provide maximum knowledge and skills to all community members.